Polyphased Inversions of an Intracontinental Rift: Case Study of the Marrakech High Atlas, Morocco. Issue 3 (7th March 2018) - Leprêtre, R.; Missenard, Y.; Barbarand, J.; Gautheron, C.; Jouvie, I.; Saddiqi, O.
Abstract: The High and Middle Atlas intraplate belts in Morocco correspond to Mesozoic rifted basins inverted during the Cenozoic during Africa/Eurasia convergence. The Marrakech High Atlas lies at a key location between Atlantic and Tethyan influences during the Mesozoic rifting phase but represents today high reliefs. Age and style of deformation and the mechanisms underlying the Cenozoic inversion are nevertheless still debated. To solve this issue, we produced new low‐temperature thermochronology data (fission track and [U‐Th]/He on apatite). Two cross sections were investigated in the western and eastern Marrakech High Atlas. Results of inverse modeling allow recognizing five cooling events attributed to erosion since Early Jurassic. Apart from a first erosional event from Middle/Late Jurassic to Early Cretaceous, four stages can be related to the convergence processes between Africa and Europe since the Late Cretaceous. Our data and thermal modeling results suggest that the inversion processes are guided at first order by the fault network inherited from the rifting episodes. The sedimentary cover and the Neogene lithospheric thinning produced a significant thermal weakening that facilitated the inversion of this ancient rift. Our data show that the Marrakech High Atlas has been behaving as a giant pop‐up since the beginning of Cenozoic inversion stages. Key Points: First large‐scale integrated low‐temperature thermochronology data sets across the High Atlas Late Cretaceous‐Cenozoic inversion of the High Atlas shows four stages of deformation, focused within the former rift Postrift inversion is facilitated through sedimentary thermal blanket, structural inheritance, and lithospheric thinning